Quality of the beam produced a pulsed ND: YAG laser - Tamuri, A. R. (2008)
The quality of the beam produced by a Nd:YAG laser was investigated. A hemispherical Nd:YAG laser resonator was developed. A flashlamp driver was designed to pump a Nd:YAG laser crystal. The output of the laser was characterized via the variation of the capacitor voltage. A phosphor card was used to detect the invisible of the infrared beam. Exposed photographic paper was utilized to examine the energetic beam after interaction. The brightness and strength of the beams were analyzed using the Matrox Inspector and VideoTest 5 software packages. The intensity of the beam produced and the volume loss after interaction were found to linearly increase with respect to the input energy